Effects of buffer composition and plasmid toxicity on electroporation-based non-viral gene delivery in mammalian cells using bursts of nanosecond and microsecond pulses - Radzevičiūtė-Valčiukė, Eivina; Gečaitė, Jovita; Balevičiūtė, Austėja; Szewczyk, Anna; Želvys, Augustinas; Lekešytė, Barbora; Malyško-Ptašinskė, Veronika; Mickevičiūtė, Eglė; Malakauskaitė, Paulina; Kulbacka, Julita; Novickij, Vitalij (Frontiers in Bioengineering and Biotechnology, 2024)
Gene electrotransfer (GET) is non-viral gene delivery technique, also known as electroporation-mediated gene delivery or electrotransfection. GET is a method used to introduce foreign genetic material (such as DNA or RNA) into cells by applying external pulsed electric fields (PEFs) to create temporary pores in the cell membrane. This study was undertaken to examine the impact of buffer composition on the efficiency of GET in mammalian cells Also, we specifically compared the effectiveness of high-frequency nanosecond (ns) pulses with standard microsecond (µs) pulses. For the assessment of cell transfection efficiency and viability, flow cytometric analysis, luminescent assays, and measurements of metabolic activity were conducted. The efficiency of electrotransfection was evaluated using two different proteins encoding plasmids (pEGFP-N1 and Luciferase-pcDNA3). The investigation revealed that the composition of the electroporation buffer significantly influences the efficacy of GET in CHO-K1 cell line. The different susceptibility of cell lines to the electric field and the plasmid cytotoxicity were reported. It was also shown that electroporation with nanosecond duration PEF protocols ensured equivalent or even better transfection efficiency than standard µsPEF. Additionally, we successfully performed long-term transfection of the murine 4T1 cell line using high-frequency nanosecond PEFs and confirmed its’ applicability in an in vivo model. The findings from the study can be applied to optimize electrotransfection conditions.